Bryophytes of Khao Kheow Open Zoo, Chonburi Province - Sukkharak, Phiangphak; Pearaksa, Pacharapol; Sarawan, Athipong; He, Si (KKU Science Journal, 2014)
An investigation of bryophyte diversity of 1.5 km nature trail, Khao Kan Rom area, Khao Je Dee area, and forest behind research centre in Khao Kheow open zoo was carried out from October 2012 to August 2013. From 265 enumerated specimens, 24 species (16 mosses, 8 liverworts) in 16 genera (10 mosses, 6 liverworts) and 13 families (9 mosses, 4 liverworts) were found. Among these the most common family of mosses was Fissidentaceae (6 species) and family of liverworts was Lejeuneaceae (5 species). In addition, of all bryophyte species found, Lejeunea anisophylla Mont. was the most common. The highest species richness of bryophytes among the four areas was found in 1.5 km nature trail.